KONSTRUKSI EXPERT ADVISOR DENGAN FIBONACCI MONEY MANAGEMENT STRATEGY MENGGUNAKAN INDIKATOR ICHIMOKU CLOUD PADA TRADING CRUDE OIL (XTIUSD) DI METATRADER 5 - Iqbal, Muhammad; Rahman, Haikal (IKRAITH-EKONOMIKA, 2025)
Crude Oil (XTIUSD) commodity trading offers significant opportunities but is accompanied by high volatility and the challenge of trader psychological bias. Trading automation through Expert Advisors (EAs) is a solution to overcome inconsistency and improve execution discipline. This study aims to construct an Expert Advisor on the MetaTrader 5 platform that integrates trading signals from the Ichimoku Cloud indicator with the Fibonacci Money Management strategy to optimize XTIUSD trading. This study uses the Research and Development (R&D) method with a V-Model approach. The EA’s performance was evaluated through two scenarios (H1 and H4 timeframes) using backtesting on 4 years of historical data (January 1, 2021 – December 31, 2024) and validated with real-time testing (August 22 – September 22, 2025). The results of the study show significant discrepancies: Scenario 1 (H1) was very profitable in backtesting (Profit Factor 1.46) but failed in real-time testing (Profit Factor 0.04), indicating a high potential for overfitting. Scenario 2 (H4) shows more stable backtesting performance (Profit Factor 1.72) and is profitable in real-time testing, albeit with a very limited sample size (1 transaction). The main conclusion is that the EA was successfully constructed, and the H4 timeframe (Scenario 2) proved to be more stable. However, the main weakness of the developed system is its strong dependence on bullish market conditions, where both scenarios only execute buy positions (long trades), making it not robust for bearish or sideways market conditions